(untitled) (Fiep Bulletin - online, 2015)
The sportive movement, as the century’s great phenomenon, has been mobilizing millions of people around the Brazil, interfering significantly in the people’s habits and the manner which various social classes act. In this way the sport complexity needs a juridical ordering that regulates and disciplines it’s relation with the society, in agreement with the definition, objectives, rights and duties, demonstrations, priorities, organization, operation and further aspects according to specific norms. However, the juridical-sportive standardization may produce positive effects or terrible consequences, depending on the hermeneutic and concern given it. However, the Brazilian legislative history demonstrates interferences, not always benefical, either by government organizations, nor by non governmental organizations, opposing legal, moral and ethical national sportive principles. In this perspective, this work at hand is to study the evolution of the brazilian sportive legislation, using as a reference the time between the New State, which was known as the period of the president Getúlio Vargas to the present political conjuncture of the today’s president Lula. This study is descriptive and documental in which the author chose to comment about bibliographical and legislative references in a manner to discuss and analyse the effects of the main legal dispositives related to the national sport, promulgated during the studied period, concluding by the significant changes that occurred, mainly the protective state action on sportive activities and practice.